2003
DOI: 10.1161/01.res.0000054624.03539.b4
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenergic Receptor–Stimulated Apoptosis in Cardiac Myocytes Is Mediated by Reactive Oxygen Species/c-Jun NH 2 -Terminal Kinase–Dependent Activation of the Mitochondrial Pathway

Abstract: Stimulation of beta-adrenergic receptors (betaARs) causes apoptosis in adult rat ventricular myocytes (ARVMs). The role of reactive oxygen species (ROS) in mediating betaAR-stimulated apoptosis is not known. Stimulation of betaARs with norepinephrine (10 micromol/L) in the presence of prazosin (100 nmol/L) for 24 hours increased the number of apoptotic myocytes as determined by TUNEL staining by 3.6- fold. The superoxide dismutase/catalase mimetics Mn(III)tetrakis(1-methyl-4-pyridyl)porphyrin pentachloride (Mn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
169
2
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(190 citation statements)
references
References 26 publications
16
169
2
3
Order By: Relevance
“…Increased caspase-3 protease activity and DNA damage indicates cardiac apoptosis and necrosis in the present study. Study have reported that 毬 -AR stimulation by catecholamine induces cardiac apoptosis or/and necrosis [31] . It has been already reported that oxidative stress provoke DNA damage (DNA fragmentation and apoptosis) and treatment with antioxidants inhibit DNA fragmentation and apoptosis [32] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased caspase-3 protease activity and DNA damage indicates cardiac apoptosis and necrosis in the present study. Study have reported that 毬 -AR stimulation by catecholamine induces cardiac apoptosis or/and necrosis [31] . It has been already reported that oxidative stress provoke DNA damage (DNA fragmentation and apoptosis) and treatment with antioxidants inhibit DNA fragmentation and apoptosis [32] .…”
Section: Discussionmentioning
confidence: 99%
“…The heart was transversely cut across the left ventricle to obtain slices no more than 0.1 cm in thickness. The heart slices were placed in the covered, darkened glass dish containing pre warmed (1%) TTC solution in phosphate buffer and the dish was incubated between 37-40 曟 for [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] min. the heart slices were turned over once or twice to make certain that it remains immersed and covered by 1 cm of the TTC solution.…”
Section: Macroscopic Enzyme Mapping (Ttc Staining)mentioning
confidence: 99%
“…Acute decompensated HF (ADHF) is the most common cause of hospitalization,3 and cardiogenic shock occurs in about 4% of ADHF admissions 4. Conventional inotropes improve haemodynamics and organ perfusion and relieve symptoms, but due to short half‐lives, they are limited to selected inpatients and outpatients with continuous infusions and are pro‐ischaemic, are pro‐arrhythmic, and may be associated with increased mortality 5, 6, 7, 8, 9…”
Section: Introductionmentioning
confidence: 99%
“…8,9 The MAPKs, mainly including JNKs, p38 kinases, and extracellular signal-related kinase 1/2 (ERK1/2), have been implicated in the pro-and antiapoptotic effects of the enhanced ␤-adrenergic signaling pathway. 10,11 However, it is not currently clear whether increased sympathetic tone directly activates the MAPKs or whether regulation occurs upstream of these molecules.…”
mentioning
confidence: 99%